Nanoarchitectured air-stable supported lipid bilayer incorporating sucrose-bicelle complex system - Tae, Hyunhyuk (2022)
Cell-membrane-mimicking supported lipid bilayers (SLBs) provide an ultrathin, self-assembled layer that forms on solid supports and can exhibit antifouling, signaling, and transport properties among various possible functions. While recent material innovations have increased the number of practically useful SLB fabrication methods, typical SLB platforms only work in aqueous environments and are prone to fluidity loss and lipid-bilayer collapse upon air exposure, which limits industrial applicability. To address this issue, herein, we developed sucrose-bicelle complex system to fabricate air-stable SLBs that were laterally mobile upon rehydration. SLBs were fabricated from bicelles in the presence of up to 40 wt% sucrose, which was verified by quartz crystal microbalance-dissipation (QCM-D) and fluorescence recovery after photobleaching (FRAP) experiments. The sucrose fraction in the system was an important factor; while 40 wt% sucrose induced lipid aggregation and defects on SLBs after the dehydration-rehydration process, 20 wt% sucrose yielded SLBs that exhibited fully recovered lateral mobility after these processes. Taken together, these findings demonstrate that sucrose-bicelle complex system can facilitate one-step fabrication of air-stable SLBs that can be useful for a wide range of biointerfacial science applications.